A new vessel motion based method for parametric estimation of the waves encountered by the ship in a seaway. - Zago, Lariuss (2022)
The present work proposes a new approach for the vessel motion-based (VMB) estimation of the sea state based on the parametric methodology. In this approach, a parametric description of the encounter wave spectrum is proposed, enabling the algorithm to solve the wave inference problem in the ship\'s reference frame. The method is tested with data obtained from numerical simulations and experimental tests, both comprising conditions with and without ship\'s forward speed. Because of its practical aspects for improving the day-to-day operational eciency and the crew\'s safety and comfort, in the more recent years, the interest in the VMB sea state inference increased signicantly. At Escola Politecnica of the University of S~ao Paulo, studies on sea state estimation (SSE) eld for stationary oating systems has been conducted since the year 2000, and more recently these studies have been expanded to include ships in a seaway. Once studying ships in operation, its forward speed must be considered and modelled in the SSE problem. Commonly, the methodologies proposed in the literature tends to carry out the wave inference already in the earth xed reference frame, and not in the ship\'s referential. This procedure leads to a greater complexity of the estimation algorithm when it tries to implement the eects of the ship\'s forward speed, in particular the uncertainties inherent to the SSE problem associated with the Doppler eect for waves reaching the ship from the stern. Recent publications presented ways to convert the encounter wave spectra to their \\absolute domain\" description. This way, if there were an analytical representation capable of describing the wide range of forms of the encounter wave spectrum, it would be possible to carry out the inference process in the ship\'s referential, using the parametric approach and avoiding several numerical considerations associated with the triple-valued problem. Here, this necessity is satised and an innovative approach is proposed where a descriptive curve for the encounter wave spectrum, based on the Weibull distribution, is introduced and studied in the context of estimating the sea states using the VMB strategy. The study carried out here was based on data obtained from the USP oceanographic vessel, Alpha Delphini. Numerical simulations on hydrodynamic numerical tools and model-scale tests on two dierent wave basins were performed, and the results achieved prove that the methodology is capable of providing expedient estimates of the waves encountered by the ship under dierent operating conditions.